2019
DOI: 10.1101/696518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DIALib: an automated ion library generator for data independent acquisition mass spectrometry analysis of peptides and glycopeptides

Abstract: Data Independent Acquisition (DIA) Mass Spectrometry (MS) workflows allow unbiased measurement of all detectable peptides from complex proteomes, but require ion libraries for interrogation of peptides of interest. These DIA ion libraries can be theoretical or built from peptide identification data from Data Dependent Acquisition (DDA) MS workflows. However, DDA libraries derived from empirical data rely on confident peptide identification, which can be challenging for peptides carrying complex post-translatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…56,57 Recent studies have shown the utility of Y-type fragment ions for quantification and generation of site-specific glycopeptide information in DIA analysis. 36,38,58 Based on these observations, we developed a rolling collision energy scheme, such that the MS/MS spectra of each glycopeptide feature also contain useful Y-type fragments for targeted re-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…56,57 Recent studies have shown the utility of Y-type fragment ions for quantification and generation of site-specific glycopeptide information in DIA analysis. 36,38,58 Based on these observations, we developed a rolling collision energy scheme, such that the MS/MS spectra of each glycopeptide feature also contain useful Y-type fragments for targeted re-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Data-independent acquisition (DIA) methods, such as SWATH-MS, have been increasingly applied in the analysis of large proteomic sample series. [28][29][30][31] In glycoproteomics, DIA approaches have been applied to assess glycosite occupancy of enzymatically deglycosylated peptides [32][33][34][35] , and more recently, facilitated the post-acquisition analysis of intact glycopeptides, either by targeted extraction of abundant Y-type (intact peptide with glycan fragments of various sizes) ions [36][37][38][39][40] or by searching against spectral libraries. 15,[41][42][43] These approaches yield remarkable depth in comparative analyses and in generating spectral libraries, generally using higher-collisional dissociation (HCD) and/or electron-based fragmentation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This oxonium ion profiling method represents an unbiased approach for a quick differentiation of multiglycosylated biotherapeutics or other glycoprotein samples. Using this approach, Phung et al (72) developed an automated ion library generator designated DIALib and profiled the oxoniomes in cell wall samples from wildtypes of yeast and its nine glycosylation mutants using the SWATH-based DIA approach. Note that, although the initial biosynthesis pathway and early processing steps before the production of Man 8 GlcNAc 2 glycan are identical in yeast and mammals, yeast tend to produce hypermannosylated glycans by adding additional mannoses (73).…”
Section: Dia On Diagnostic Glyco-oxonium Ionsmentioning
confidence: 99%
“…For data‐independent MS/MS acquisition (DIA) mode, a software termed DIALib was introduced to automate the creation of peptide and glycopeptide DIA ion libraries. DIALib's theoretical ion libraries were able to identify N‐ and O‐glycopeptides from yeast and mammalians without prior knowledge of their glycan structures (Phung, Zacchi, et al, 2020).…”
Section: Developments In Glycoproteomics Data Analysismentioning
confidence: 99%